Flash Player 9 (or above) is needed to view presentations.
We have detected that you do not have it on your computer. To install it, go here.

Int Math 2 Section 3-1 1011

• 771 views

Equations and Formulas

Equations and Formulas

More in: Education , Technology
• Comment goes here.
Are you sure you want to
Be the first to comment
Be the first to like this

Total Views
771
On Slideshare
0
From Embeds
0
Number of Embeds
2

Shares
4
0
Likes
0

No embeds

Report content

No notes for slide

Transcript

• 1. Chapter 3 Equations and Inequalities
• 2. Section 3-1 Equations and Formulas
• 3. Essential Questions ✤ How do you determine if a number is a solution of an equation? ✤ How do you solve an equation or a formula? ✤ Where you’ll see it: ✤ Travel, safety, physics
• 4. Vocabulary 1. Equation: 2. True Equation: 3. False Equation: 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
• 5. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: 3. False Equation: 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
• 6. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
• 7. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: 5. Solution of the Equation: 6. Solve an Equation:
• 8. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: An equation with a variable 5. Solution of the Equation: 6. Solve an Equation:
• 9. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: An equation with a variable 5. Solution of the Equation: The value that makes the equation true 6. Solve an Equation:
• 10. Vocabulary 1. Equation: A statement where two numbers or expressions are equal 2. True Equation: Both sides have the same numerical expression 3. False Equation: When the numerical expressions are not equal 4. Open Sentence: An equation with a variable 5. Solution of the Equation: The value that makes the equation true 6. Solve an Equation: Find the values that make it true by isolating the variable
• 11. Formula
• 12. Formula An equation (rule) that states a relationship between two or more quantities
• 13. Formula An equation (rule) that states a relationship between two or more quantities We can solve for any part of a formula!!!
• 14. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5
• 15. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x
• 16. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x
• 17. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x
• 18. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7
• 19. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3
• 20. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4
• 21. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2
• 22. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2 x=2
• 23. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2 x=2 14(2) + 3 = 12(2) + 7
• 24. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 −3 −3 2x = 4 2 2 x=2 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 25. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 2 2 x=2 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 26. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 x=2 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 27. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 28. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 29. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 30. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 31. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 32. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 x = −1 2 2 2 x=2 3 =9 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 33. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 x = −1 2 2 2 x=2 3 =9 3(−1) + 8 = 5 2 (−3) = 9 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 34. Example 1 Using only the numbers from {-3, -2, -1, 0, 1, 2, 3}, determine the solution(s) of each equation. 2 a. 14x + 3 = 12x + 7 b. x = 9 c. 3x + 8 = 5 −12x −12x −8 −8 2x + 3 = 7 2 x =± 9 3x = −3 −3 −3 3 3 2x = 4 x = ±3 x = −1 2 2 2 x=2 3 =9 3(−1) + 8 = 5 2 (−3) = 9 −3 + 8 = 5 14(2) + 3 = 12(2) + 7 28 + 3 = 24 + 7
• 35. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23
• 36. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3
• 37. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 b = 17
• 38. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 b = 17 17 − 3 = 14
• 39. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 17 − 3 = 14
• 40. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 1 m= 5 17 − 3 = 14
• 41. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 1 m= 5 17 − 3 = 14 1 (45) = 9 5
• 42. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 b = 17 1 m= 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
• 43. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 m= 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
• 44. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
• 45. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 1 (45) = 9 5 45 =9 5
• 46. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 w=4 1 (45) = 9 5 45 =9 5
• 47. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 w=4 1 (45) = 9 5 4(4) + 7 = 23 45 =9 5
• 48. Example 2 Solve each equation. a. b − 3 = 14 b. 45m = 9 c. 4w + 7 = 23 +3 +3 45 45 −7 −7 b = 17 1 4w = 16 m= 4 4 5 17 − 3 = 14 w=4 1 (45) = 9 5 4(4) + 7 = 23 45 16 + 7 = 23 =9 5
• 49. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101
• 50. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation
• 51. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6
• 52. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x −3x
• 53. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5
• 54. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5
• 55. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1
• 56. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both sides to get all of the x’s on the same side of the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1 Check!
• 57. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1 Check!
• 58. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 −3x − 5 −3x − 5 x=1 Check!
• 59. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 x=1 Check!
• 60. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 Check!
• 61. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 18 18 Check!
• 62. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 18 18 Check! a=6
• 63. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. a. 4x + 5 = 3x + 6 b. 18a − 7 = 101 Subtract 3x from both Add 7 to both sids to sides to get all of the get the variable term x’s on the same side of by itself the equation 18a − 7 = 101 4x + 5 = 3x + 6 +7 +7 −3x − 5 −3x − 5 18a = 108 x=1 18 18 Check! a=6 Check!
• 64. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40
• 65. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated
• 66. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42
• 67. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6
• 68. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6 x−5=7
• 69. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6 x−5=7 +5 +5
• 70. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work on getting the variable isolated 6(x − 5) = 42 6 6 x−5=7 +5 +5 x = 12
• 71. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 6(x − 5) = 42 6 6 x−5=7 +5 +5 x = 12
• 72. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 6 6 x−5=7 +5 +5 x = 12
• 73. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 x−5=7 +5 +5 x = 12
• 74. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 7g = −28 x−5=7 +5 +5 x = 12
• 75. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 7g = −28 x−5=7 7 7 +5 +5 x = 12
• 76. Example 3 State what the ﬁrst step to solving each equation would be and how you know you should do that step. Then solve. c. 6(x − 5) = 42 d. 7g − 12 = −40 Divide by 6 to work Add 12 to isolate the on getting the variable term variable isolated 7g − 12 = −40 6(x − 5) = 42 +12 +12 6 6 7g = −28 x−5=7 7 7 +5 +5 x = 12 g = −4
• 77. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5
• 78. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5
• 79. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5 F = 77.4 + 32
• 80. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5 F = 77.4 + 32 F = 109.4
• 81. Example 4 The formula for converting from degrees Celsius to degrees Fahrenheit is given below. Convert 43°C to °F. 9 F = C + 32 5 9 F = (43) + 32 5 F = 77.4 + 32 F = 109.4 43°C is 109.4°F
• 82. Problem Set
• 83. Problem Set p. 106 #1-37 odd “The greatest challenge to any thinker is stating the problem in a way that will allow a solution.” - Bertrand Russell